Effects of a Weak Intrinsic Magnetic Field on Atmospheric Escape From Mars. Issue 18 (21st September 2018) - Sakai, Shotaro; Seki, Kanako; Terada, Naoki; Shinagawa, Hiroyuki; Tanaka, Takashi; Ebihara, Yusuke
Abstract: The magnetization of a planet significantly changes the nature of atmospheric escape, and the question of whether a planetary field shields atmosphere from erosion by the solar wind or not remains open. Ion escape processes from Mars are investigated under two hypothetical conditions, namely, no intrinsic magnetic field and weak intrinsic dipole field cases under present solar wind conditions based on multispecies magnetohydrodynamics simulations. The existence of a weak dipole field results in an enhancement of the tailward flux of planetary ions through the four escape channels. Two channels are associated with the open fields at the poles, and the others are caused by magnetic reconnection between the planetary and solar wind magnetic fields at the flank magnetopause. The ion escape rate with the weak dipole is greater than in the no‐dipole case. The enhancement is significant for O2 + and CO2 +, suggesting ion escape from the low‐altitude ionosphere. Plain Language Summary: Present Mars has a thin atmosphere and little water on the surface. Space missions have provided some evidences for the existence of liquid water and a thick atmosphere on ancient Mars. These evidences suggest Mars has experienced significant atmospheric loss up to the present. Ion outflow is one of the important atmospheric loss mechanisms. In the present day, Mars does not have a global magnetic field such as that of Earth, and thus, ions escape by the direct interaction with the solar wind (influenced to some extent by Mars' crustal fields). In contrast, it is expected that ancient Mars had a global magnetic field. The global magnetic field forms the magnetosphere around the planet, perhaps changing the ion escape mechanisms. In this study, a numerical simulation of the Mars‐solar wind interaction is used to compare ion escape for the case of no planetary field with a case where a weak global magnetic field is assumed. The weak global magnetic field yields four escape routes associated with open magnetic fields and magnetic reconnection. The escape rate of heavy ions increases by ~25% compared to the nondipole case, particularly facilitating the escape of O2 + and CO2 + present in the low‐altitude ionosphere. Key Points: The ion escape rate increases when a weak intrinsic dipole magnetic field is introduced The weak intrinsic field facilitates four escape routes, through cusps and magnetic reconnections between the IMF and planetary fields The enhancement of the escape rate is more pronounced for O2 + and CO2 + than O +, suggesting the ion escape from the low‐altitude ionosphere